1992
DOI: 10.1007/bf00917626
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and reversal of experimental colitis by a monoclonal antibody which inhibits leukocyte adherence

Abstract: The role of neutrophils in the pathogenesis of acute colitis was investigated using a rabbit model. Colitis was induced by intracolonic administration of trinitrobenzene sulfonic acid in 30% ethanol. Myeloperoxidase activity was measured at various times after induction of colitis as an index of neutrophil infiltration, and this was confirmed by histology. The permeability of the colonic epithelium to [51Cr]EDTA was also measured at various times after induction of colitis. The most marked increase in neutroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…[41][42][43][44] Few studies have directly examined the role of these molecules during experimental colitis with these reports documenting modification of trinitrobenzene sulfonic acid (TNBS) colitis with anti-CD18 or CD11b/ CD18 antibodies. 45,46 We report here that the b 2 integrin LFA-1 (CD11a/CD18) plays an important pathological role, whereas Mac-1 (CD11b/CD18) provides a critical regulatory role in DSS-induced experimental colitis. Several possible explanations could account for the difference in outcome regarding CD11b.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44] Few studies have directly examined the role of these molecules during experimental colitis with these reports documenting modification of trinitrobenzene sulfonic acid (TNBS) colitis with anti-CD18 or CD11b/ CD18 antibodies. 45,46 We report here that the b 2 integrin LFA-1 (CD11a/CD18) plays an important pathological role, whereas Mac-1 (CD11b/CD18) provides a critical regulatory role in DSS-induced experimental colitis. Several possible explanations could account for the difference in outcome regarding CD11b.…”
Section: Discussionmentioning
confidence: 99%
“…The double adhesion molecule deficiency (Pselectin/ICAM-1) followed the same trend. It is intriguing that acute administration of anti-adhesion therapy reduced mucosal dysfunction in TNBS-induced colitis in rabbits, but this was examined over 24 h, not longer [34]. The difference may be related to acute treatment with antibody versus more long-term therapy in these adhesion molecule-deficient animals.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it implies that disruption of these processes could attenuate the inflammatory infiltrate. Indeed, one report has indicated that monoclonal antibodies targeted to CDl 1 / 18 ameliorated inflammation in a rodent model of colonic inflammation induced by an exogenous agent (26).…”
Section: Introductionmentioning
confidence: 99%